Suspicions of Distorting of the Noble Qur’an and the Evidence for its Invalidity - Ali Mohsen Jebir (lark, 2021)
The scientific evidence confirms the fact that the Qur’an is protected from distortion,it is a coherent, independent entity, it was not reached by the hand of distortion. The Qur’an changes an emergency purpose, nor sudden aggression. The issue of the integrity of the Qur’an text requires the refutation of any different claims, the rejection of any adverse trend, this calls for a refinement of the claims of distortion and refuting their falsehoods from all sides. We find the claims of distortion are move between allegations, assumptions, single news, accusations, suspicions, and attempts when we filtrate them and examine their states . the Monitoring these phenomena necessitates that the subject goes along with its particulars, and when the subject goes along with its particulars and phenomena, it becomes clear that some of them are invalid, the other part fails, and the last part fails to achieve the case. We say: abrogating rulings is one thing, and distortion is another thing. Abrogation is not a distortion, but rather it is a substitution of a ruling in the place of a ruling, or a lifting of a ruling from God Almighty, to alleviate the servants, or to take care of the interests of Muslims, or to dispense with a timed ruling by a permanent ruling. There is no way to challenge in this respect the allegation of distortion in the Qur’an ..